ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI LIKUIDITAS BANK SYARIAH DI INDONESIA MENGGUNAKAN METODE VECTOR ERROR CORRECTION MODEL (VECM) - AYIF FATHURRAHMAN; FIRSHA RUSDI (Prodi Manaj. Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam – UIN Imam Bonjol Padang, 2019)
This study aims to analyze the factors that affect the liquidity of Islamic banks in Indonesia. The analysis is carried out using sequential monthly data published by Bank Indonesia in the period 2010 to 2018. The variables used are internal factors (Capital Adequacy Ratio (CAR), Return On Assets (ROA)) and external factors (SBI Inflation and Interest Rates) ) The method used in this study is the Vector Error Corection Model (VECM). Based on the results of the study show that in the short term, the variable CAR, ROA, Inflation and SBI interest rates positively and significantly affect FDR. Whereas in the long term, the CAR variable and inflation have a significant positive effect on FDR, the ROA variable negatively influences FDR. And the variable SBI interest rate does not have a significant effect on FDR.